TEACHING THE MODULE “STRUCTURE AND PRINCIPLE OF OPERATION OF HIGH FREQUENCY GENERATORS” USING THE “ROLE PLAY” METHOD (Web of Technology: Multidimensional Research Journal, 2024)
The article deals with the role-playing technology and the role of modern teaching and role models and interactive methods used to teach the module “Strukture and working principles of Hing frequency generator”. The second part includes theoretical and practical training modules concerning “Strukture and working principles of Hing frequency generator”, and the didactic developments for independent learning.